O ESCRITÓRIO DE GERENCIAMENTO DE PROJETOS COMO FERRAMENTA PARA IMPLANTAÇÃO DA GESTÃO DO CONHECIMENTO EM UMA INSTITUIÇÃO FEDERAL DE ENSINO - Huback, Cristina Knupp (2014)
Great challenges of our time to the activities developed by education institutions are strongly related to the deep and continuous transformations arising from the speed which new knowledge is generated. The object of study is a Public Center of Technological Education whose mission is teaching, research and extension; therefore, it is essential to the process of creation and transmission of knowledge. In this work, we intend to propose the implementation of a Project Management Office (PMO) as a tool for knowledge management in the context of Scientific Research developed in the Center. The research has an exploratory and descriptive, seen to associate topics such as Knowledge Management, Project Management Office (PMO) and Education Institution. The work constructed from literature review, desk research and field. The contributions of the subject are in possibility of reflection on the theories of Knowledge Management and PMO applied to an educational institution. The paper conclude that Knowledge Management although originating from the private sector it s employed in teaching institutions. Furthermore, the work indicates elements for structuring a Virtual PMO specifically with regard to interaction and knowledge transfer in the field of scientific research developed by the institution object of study.